2009
DOI: 10.1095/biolreprod.109.078261
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Bisphenol-A Exposure Alters Rat Reproductive Development and Ovarian Morphology Without Impairing Activation of Gonadotropin-Releasing Hormone Neurons1

Abstract: Developmental exposure to endocrine-disrupting compounds is hypothesized to adversely affect female reproductive physiology by interfering with the organization of the hypothalamic-pituitary-gonadal axis. Here, we compared the effects of neonatal exposure to two environmentally relevant doses of the plastics component bisphenol-A (BPA; 50 microg/kg and 50 mg/kg) with the ESR1 (formerly known as ERalpha)-selective agonist 4,4',4''-(4-propyl-[(1)H]pyrazole-1,3,5-triyl)trisphenol (PPT; 1 mg/kg) on the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
150
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(170 citation statements)
references
References 88 publications
16
150
4
Order By: Relevance
“…This indicates that developmental exposure to a human-relevant mixture of environmental contaminants advances reproductive senescence. This has previously been described by others for high doses of single chemicals (Armenti et al 2008, Adewale et al 2009). The process of follicle assembly and the recruitment of primordial follicles in the ovary to enter into growth are thought to be essential for the duration of the reproductive lifespan (Uzumcu & Zachow 2007, Crain et al 2008, Diamanti-Kandarakis et al 2009).…”
Section: Reproductive Aging In Females and Pituitary Gland Changessupporting
confidence: 57%
See 1 more Smart Citation
“…This indicates that developmental exposure to a human-relevant mixture of environmental contaminants advances reproductive senescence. This has previously been described by others for high doses of single chemicals (Armenti et al 2008, Adewale et al 2009). The process of follicle assembly and the recruitment of primordial follicles in the ovary to enter into growth are thought to be essential for the duration of the reproductive lifespan (Uzumcu & Zachow 2007, Crain et al 2008, Diamanti-Kandarakis et al 2009).…”
Section: Reproductive Aging In Females and Pituitary Gland Changessupporting
confidence: 57%
“…The hypothalamic-pituitaryovarian axis is involved in the processes of reproductive aging in females, and reprograming of the hypothalamic-pituitary-ovarian axis may also be involved in premature reproductive senescence (Gore et al 2011). All chemicals included in the mixture have been shown to affect either estrogen or androgen actions, and some are capable of interfering with folliculogenesis or follicle health in the ovary (Crellin et al 2001, Adewale et al 2009, Rodríguez et al 2010, Ahn et al 2012, Wang et al 2012, Zhang et al 2013). Thus, direct or indirect mixture effects on the ovaries resulting in early reproductive aging are plausible.…”
Section: Reproductive Aging In Females and Pituitary Gland Changesmentioning
confidence: 99%
“…As a result, the percentage of animals showing abnormal estrous cycles increased with age in the BPA groups, but the rate was similar to that in the control group. It was demonstrated that abnormal ovarian cycles occurred in rats exposed perinatally to high doses (1.2 mg/kg or 50 mg/kg) of BPA (Adewale et al, 2009;Rubin et al, 2001). However, our data suggest that low doses of BPA, based on the U.S. EPA reference dose or less, do not induce abnormal estrous cycles in mice, even when the estrous cycles were observed during the aging period.…”
Section: Discussioncontrasting
confidence: 64%
“…Although bisphenol A (BPA) is widely evaluated in endocrine disruptor studies, the ovarian aging (Adewale et al, 2009;Rubin et al, 2001) and immune function (Yoshino et al, 2004) of the animals exposed to low doses of BPA are not well known. Therefore, the observation of estrous cycles during the aging period was examined in C57BL/6J mice neonatally treated with BPA.…”
Section: Introductionmentioning
confidence: 99%
“…When treatment starts postnatally after 15 days, age at VO is not affected (Nikaido et al, 2005;Laws et al, 2000). During the age window comprised between birth and 15 days, age at VO is either not affected (Nagao et al, 1999;Adewale et al, 2009;Losa-Ward et al, 2012;Yu et al, 2010) or early (Adewale et al, 2009;Losa-Ward et al, 2012;Fernandez et al, 2009;Nah et al, 2011). A dose of 50 µg/kg causes advancement of puberty while 50 mg/kg has no effect, indicating a non-linear doseresponse relationship (Adewale et al, 2009;Losa-Ward et al, 2012).…”
Section: Female Rodentmentioning
confidence: 99%